UNIVERSITÀ TRA NUMERI E SCELTE Le opinioni degli studenti su futuro, didattica, relazioni, etica e altro - Lugaresi, Nicola (Interventi, 2021)
This book is the result of a large survey submitted to a group of students of the Faculty of Law of the University of Trento. The survey dealt with various topics: future, university, teaching, teachers, students, personal choices, ethics, community. Starting from the results of the survey, we try to understand not only what is the opinion, and even before that the "feeling" of the students, but also what can be revised in the academic world, with particular regard to its principles and values, interpersonal relationships, and the objectives of teaching. The book is aimed at students, faculty, members of decision-making bodies, at different levels, and, ultimately, anyone with an interest in university issues.